Bound States of Spinless Particles in a Short-Range Potential - Hassanabadi, Hassan; Castro, Antonio Soares de [UNESP] (Walter De Gruyter Gmbh, 2015)
With a general mixing of vector and scalar couplings in a two-dimensional world, a short-range potential is used to explore certain features of the bound states of a spinless particle. Bound-state solutions are found in terms of the Gauss hypergeometric series when the potential parameters obey a certain constraint relation limiting the dosage of a vector coupling. The appearance of the Schiff-Snyder-Weinberg effect for a strong vector coupling and a short-range potential as well as its suppression by the addition of a scalar coupling is discussed.
Keywords: Bound-State Solutions; Schiff-Snyder-Weinberg Effect; Spinless Particle